CONTRIBUTION OF SOCIAL CAPITAL TO THE PERPETRATORS OF STUDENT ACTIVITY UNIT IN AN EFFORT TO GROW THE SOUL OF ENTREPRENUR IN STUDENTS OF PGRI ADI BUANA UNIVERSITY SURABAYA - Martha Suhardiyah; Subakir Subakir; Luqmanul Hakim; Andri Kurniawan (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
A person's ability to interact with others in a community is social capital. Social ability that occurs and is based on trust, mutual understanding, and rules about the same values can be understood (shared value) owned by group members in order to be resilient to life's challenges. Student Activity Unit (UKM) is a student organization in the campus environment aims to create activities outside the academic students who are thought / reasoning, talent interests, welfare, and special interests in addition to equipping softskil for its members can develop. The result of data analysis shows that there are 1)Influence of Social Capital variables in the form of Participation, Social Norm on Student Activity Units (SMEs) 2). There is an influence of capital social variables in the form of Participation, Social Norm on the soul of Entrepenuer 30. There is an influence of capital social variables in the form of Participation, Social Norm on the soul of Entrepenuer through the Student Activity Unit